ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN DI WARKOP SEHATI PANGKALAN ASEM - Salman, Muhammad; S. Devina De Fretes, Mercy (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research was based on a problem where Warkop Sehati experienced a decline in sales due to several reasons. The aim of this research is to find out and analyze the marketing strategies implemented by Warkop Sehati Pangkalan Asem in increasing sales. The method in this research uses a qualitative descriptive method. This research data collection technique uses observation, interviews, and documentation methods. The results of the research show that the marketing strategy implemented by Warkop Sehati has been carried out quite well, although it has not been optimal because several inhibiting factors have been encountered, including an increase in standard prices, a less strategic location and limited parking space, less than optimal promotion. The supporting factors include the menu offered being varied, unique and new while still prioritizing quality and taste, the prices are quite affordable, the room atmosphere is comfortable and has a classic nuance and is supported by adequate facilities.